ANALISIS PERHITUNGAN DAN PEMOTONGAN PAJAK PENGHASILAN FINAL PASAL 4 AYAT (2) ATAS JASA SEWA TANAH DAN/BANGUNAN PADA PT. ANGKASA PURA I (Persero) MAKASSAR - Fiqram Ramadhan Effendy; Lina Mariana (Jurnal Riset Perpajakan: Amnesty, 2021)
This study aims to determine the calculation and withholding of final income tax article 4 paragraph 2 on land and/building rental services (space lease) carried out at PT. ANGKASA PURA I (Persero). The type of research used is a method with a qualitative approach. Qualitative data is data in the form of numbers used in this study such as evidence of income tax collection and tax deductions for specific airport services for land and/or building leases. After conducting the analysis and discussion, the authors conclude that the withholding of the final income tax article 4 paragraph 2 of land and / building rental services (space rental) at PT.Angkasa Pura I (Persero) is in accordance with the provisions of the KMK. No120/KMK.03/2002 using a rate of 10% with a tax base (DPP) of the gross amount of the rental value